From Gaza to Unity of The Ummah: Uncovering Potential of The Geopolitics of Ummah - Noormansyah, Reza; Nabiha, Keysa Neva; Fany, Alfa Sofia; Ulhasanah, Nida; Hanifah, Asma’ Zakiya (Perhimpunan Intelektual Muslim Indonesia, 2024)
This study explores the potential of the geopolitics of ummah in uniting the Muslim community amidst the ongoing genocide in Gaza since October 2023. This genocide has sparked global support, including from Western societies. Given Palestine's status as the home of Al-Aqsa Mosque, the third holiest site in Islam, this momentum should spur the ummah to make a significant impact. The study underscores the need for the ummah to realize their potential, as demonstrated historically and through Western responses to their unity efforts. We examine this potential using the Baitul Maqdis Barakah Circle ). Data were obtained from literature studies and analyzed using critical discourse analysis (CDA) to understand how this discourse influences the thoughts and behaviors of the ummah. The results indicate that support for Palestine has heightened awareness of the liberation of thought. Islamic solutions, including struggle in the way of Allah, are gaining recognition as responses to the failure of international actors to end the Israeli occupation. These findings suggest that the ummah can play a significant role in global politics by uniting and mobilizing their strengths, including population numbers, comprehensive solutions to occupation, and material power such as natural resources and military capabilities.